ANTIBIOTIC COMBINATIONS WITH COLISTIN AGAINST CARBAPENEM-RESISTANT Klebsiella pneumoniae - in vitro ASSESSMENT - Yuliya Marteva-Proevska; Tzvetan Velinov; Rumyana Markovska; Diliyana Dobrikova; Ivan Pavlov; Lyudmila Boyanova; Ivan Mitov (Peytchinski Publishing, 2018)
Purpose: The treatment of infections, caused by highly resistant strains of Gram-negative bacteria is extremely difficult. A potentially valuable option is combination antibiotic therapy. The aim of this study was to evaluate three different in vitro methods for synergy testing and to assess the effect of different combinations with colistin against carbapenem-resistant K. pneumoniae strains. Material/methods: A screening test for synergy with colistin (developed in the laboratory) and the microdilution method of El-Azizi were used on 50 carbapenem-resistant strains of K. pneumoniae. Additionally, time-kill assays (TKA) were performed for one antibiotic combination. Results: A total of 16 combinations were tested with the screening test. Synergy and probable synergy with colistin were observed mainly with azithromycin (18% of the isolates), rifampicin (16%), meropenem (14%) and doxycycline (12.8%). The combinations colistin-rifampicin, colistin-meropenem and colistin-gentamicin, were synergistic in 36%, 8% and 20%, respectively, according to the microdilution method of El-Azizi. The observed synergy was detected mainly against some of the colistin resistant strains. Agreement between the two methods was found in 80% for the combinations colistin-rifampicin and colistin-meropenem and in 84% for colistin-gentamicin. Agreement between the three methods used was observed for four strains (80%). Conclusions: The screening test may represent a rapid and cost effective screening of a large number of combinations with colistin. The microdilution method of El-Azizi may provide an opportunity for rapid testing of three double and one triple antibiotic combinations in one plate. There is an urgent need for standardization of the methods for synergy testing and guidelines for diagnostic laboratories.